Analisis Nilai-Nilai dalam Tradisi Sulang-Sulang Hariapan: Sebuah Perspektif Teologi Kristen - Geovando Siahaan (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
The sulang-sulang hariapan tradition is a significant cultural heritage of the Batak Toba community that embodies values of love, respect for elders, family reconciliation, equitable inheritance distribution, and leadership regeneration. The ritual is traditionally performed by offering food to parents who have reached the status of saur matua, symbolizing gratitude and respect. It is also accompanied by requests for blessings, advice, and public acknowledgment of mistakes, thus fostering peace, forgiveness, and social harmony within the community. However, in contemporary practice, the meaning of this tradition has gradually shifted toward a more formalized ceremony that emphasizes social status rather than its original spiritual and communal values. This study employs descriptive qualitative methods, combining field research with theological reflection, to examine how the values inherent in sulang-sulang hariapan can be understood in the light of the Gospel. The findings indicate that the tradition has profound potential to serve as a contextual medium for Christian faith expression. Therefore, it is crucial to revitalize its theological meaning so that the tradition remains relevant and transformative in strengthening family bonds and nurturing leadership in the modern era.